Evolution and Trend of Alternative Internal Combustion Motor Control Systems, Literature Review - Juan Trujillo-Tello, Juan Trujillo-Tello (2020)
This work makes a comparison between different studies related to the operation of internal combustion engines. The behavior of the engine is strictly governed by the different control systems among which it has an electronic injection, variable distribution systems, turbines of variable geometry, among others. This type of system is in charge of making the different adaptations to achieve the operating conditions and the requirements that are demanded of the engine in various driving situations. The power demand, the emission limit required by the different standards, as well as the confidence and security required by the users of these engines, depend directly on the control system that has been implemented. Currently, electronic control systems are based on the processing of digital and analog data derived from the measurements of the different receiving sensors directly from the motor, and whose information determines the activation of the actuators according to the motor's operating parameters. immersed within the cartography that has been designed for each case. Electronic systems, due to their importance and their wide margin of control with respect to mechanical elements in the engine, need to be calibrated and directed by the software.